PAI Teachers and the Phenomenon of Spiritual Quiet Quitting: A Study on the Decline of Students' Worship Motivation Amid Academic Curriculum Density - Sesilia Marsya Nabila Zahara; Rice Putri Dia Utami; Muhammad Yasin Abdul Aziz Rantisi Nasution; Lety Febriana (LP2M IAIN Palopo, 2026)
The transformation of academic curricula demanding intensive cross-disciplinary competencies has produced a density of learning agendas with implications for students' psychological and spiritual dimensions. This phenomenon gives rise to a condition conceptualized as